NEW LIFE FROM A PASTORAL TEXT OF TERROR? GENDER PERSPECTIVES ON GOD AND HUMANITY IN 1 TIMOTHY 2 - Mouton, Elna (Scriptura, 2012)
Amidst threatening pseudo-practices, 1 Timothy seems to be concerned mainly with the integrity of the Christian gospel within the larger Greco-Roman society. To account for its rich yet complex world view, the intertextual coherence of 1 Tim 1:15-3:1 is investigated - with special reference to gender images from Gen 2-3 in 1 Tim 2:13-15. In an attempt to make sense of the utterances regarding women in 2:8-15, and particularly the explanation in 2:13-15, the essay explores two main sets of arguments. A first view explores the implications of a literal interpretation of 1 Tim 2:13-15. It argues that the author contrasted the thinking of Gen 2-3 by importing a limited selection from it into his letter - a strategy bearing the risk of being incompatible with the theological thrust of both 1 Tim and Gen 1-3. A second view argues that 1 Tim 2:13-15 served as an allegory, and that Adam and Eve, as well as the image of childbearing, functioned metaphorically as motivation for moral behaviour. The essay concludes that 1 Tim 2:8-15 is a context-specific appro-priation of the creation story rather than a universal statement on the relationship between women and men. It pleads for a life-giving rhetoric that either uses 1 Timothy’s theological thrust as a lens for interpreting 2:8-15 or accepts (some aspects of) it as irretrievably patriarchal and violent, yet allowing it to function as a mirror for on-going discussions on human dignity and the integrity of creation. doi: 10.7833/111-1-38